PERSONALITY TRAITS OF WOMEN AGROPRENEURS - V. Darling Selvi, Dr.P. Jegan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Personality is made up of the characteristic patterns of thoughts, feelings and behaviors that make a person unique.Personality traits are complex, genetically co-determined psychophysiological characteristics of an individual manifested in a consistent way of behaving in a wide variety of situations.Openness to experience means a tendency to be creative, curios, adventurous and receptive to new experience.Entrepreneurs are known for what they do: they create new products, processes, and services for the market. Women in general and women entrepreneurs in particular play a major role in the economic development of the nation.Agropreneurs are those who involved in agriculture business. The present study deals with the personality traits of 240 women agropreneurs who established their enterprises in Kanyakuari district. The researcher used ANOVA and Cronbach’s Alpha to test the reliability of the 25 statements taken for study KMO and Bartlett’s Test to test the sample adequacy, Factor Analysis to locate the components, Transformation Matrix to know the inter relationship of the factors and Scree Plot to project the slope of the components. The analysis were carried out with the help of SPSS. The study shows thatThe Personality Traits of Women Agropreneurs were categorised into Challengers, Opportunists and Innovators as per rotated factor analysis. It is observed from the analysis that that the Innovators have close association with Opportunists.